Sastra dan Islam Catatan Seputar Dialektika Sistem Nilai - Helmi Syaifuddin (UIN Maulana Malik Ibrahim Malang, 2002)
Literature and Islam are two entities that do not have to be related. Due to the fact, literature can develop and flourish without any Islamic emblems in it. Even if there is a connection, the relationship between literature and Islam is actually very problematic. That is because the Islamic dustur (al-Quran), as a source of inspiration that complements every aesthetic momentum in Islamic civilization, expressly requires the integration of two totally different world existence in a space of beauty. This paper deals with the dialectic between the literary and Islamic value systems. Semiology of Islamic literature is spelled out in two aspects of meaning that are individual and universal. Individual interpreted Islamic literature has a subordinate attachment to religion while the universal interpreted by Islamic literature has unlimited opportunities of space and time to move and find spiritual meaning in life. Sastra dan Islam adalah dua entitas yang tidak harus ada kaitannya. Karena kenyataannya, sastra dapat tumbuh subur dan berkembang tanpa harus ada embel-embel Islam di dalamnya. Kalaupun ada kaitannya, hubungan antara sastra dan Islam sesungguhnya sangat problematis. Hal itu dikarenakan dustur Islam (al-Quran), sebagai sumber inspirasi yang melengkapi setiap momentum estetik dalam peradaban Islam, dengan tegas mensyaratkan adanya keterpaduan antara dua eksistensi dunia yang benar-benar berbeda dalam sebuah ruang keindahan. Tulisan ini menyinggung dialektika antara sistem nilai sastra dan Islam. Semiologi sastra Islam termantrakan dalam dua segi makna yang bersifat individual dan universal. Individual dimaknai sastra Islam memiliki keterikatan subordinatif terhadap agama sedangkan universal dimaknai dengan sastra Islam memiliki peluang tak terbatas ruang dan waktu untuk bergerak menemukan makna spiritual dalam kehidupan.